THE LEARNING OF KHAT AL ARABI AT THE AL-HUSNA MARINDAL ISLAMIC BOARDING SCHOOL IN INCREASING THE LEARNING INTEREST OF GRADE VIII STUDENTS - Sari, Meysah Wanda; Zein, Achyar (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study aims to find out the learning of khat ar-rabi at the Al-husna Marindal Islamic boarding school in increasing the learning interest of grade VIII students. This study uses a qualitative research method with a case study approach. Data collection techniques are carried out through observation, interviews, and documentation. The data obtained was then analyzed descriptively.this research was carried out at the AL-Husna Marindal Islamic Boarding School, Khat Learning is also included in the maharah kitabah. The research wanted to find out how the students in increasing their interest in learning khat in grade VIII and the students were not able to write neatly. The learning of khat al-arabi at the Al-Husna Marindal Deli Serdang Islamic Boarding School also aims to increase the awareness and skills of students in various aspects, such as awareness of religious values and skills in creating beautiful works of art. Class VIII students who take part in khat learning in their class only some like and others do not like khat learning and there are several factors, namely lack of awareness for interest in participating in khat learning. Types of methods in khat : demonstration method, copying method, plagiarizing method, lecture method and assignment method. Khat learning at the Al-husna Marindal Islamic boarding school to increase the learning interest of students/students can use Effective Learning methods, student involvement, planning and evaluation, individual skills.